Upaya Meningkatkan Minat dan Hasil Belajar IPS Menggunakan Metode Teka-Teki Silang di Kelas VIII A SMPN 2 Kumai - Katino Katino (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
This research was conducted in class VIII A of SMPN 2 Kumai by applying the Crossword Puzzle learning method to determine the increase in student interest and learning outcomes. Data collection techniques using observation, field notes, and documentation. The types of data collected are observational data on interest in learning and data on group learning outcomes. The data analysis technique used is the qualitative data analysis technique which consists of data reduction, data presentation, and conclusion drawing.